A welding wire for welding high-pressure hydrogen transmission pipeline steel and a preparation method and application thereof

CN122875984APending Publication Date: 2026-10-09JIANGSU UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611283684.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

其三,该工艺难以适用于管道全位置自动化高效焊接,且多层多道焊时层间清理与焊剂回收繁琐,施工效率受限

Benefits of technology

[0024]有益效果:与现有技术相比,本发明具有以下显著优点:(1)本发明焊接效率高,通过激光与MAG电弧旁轴复合,实现高能量密度与宽熔宽协同作用,在相同热输入下相比埋弧焊焊接效率提高5倍以上;间隙兼容性强,电弧辅助加热可有效弥补激光对间隙敏感性高的不足,允许装配间隙达1.5~2.0 mm,显著降低工件坡口加工与组对精度要求;热影响区窄,相比常规的埋弧焊接,热影响区缩短至1/4。(2)本发明充分利用了激光-电弧复合热源、C/Mn/Mo/Ni/Al/Zr元素焊接冶金行为、CO2在复合热源分解及氧化作用,将三者有机结合,形成1+1+1>3的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875984A_ABST
    Figure CN122875984A_ABST
Patent Text Reader

Abstract

The application discloses a welding wire for high-pressure hydrogen pipeline steel welding, a preparation method and application thereof, and the welding wire comprises the following components in percentage by mass: C: 0.07-0.1%, Si: 0.4-0.8%, Mn: 1-1.7%, P: 0.001-0.01%, S: 0.01-0.03%, Cr: 0.01-0.1%, Mo: 0.2-0.4%, Ni: 0.6-0.9%, Al: 0.01-0.09%, Zr: 0.01-0.05%, and the balance is Fe. The laser-MAG composite welding is adopted, and the welding efficiency is high by using the welding wire; compared with submerged-arc welding, the welding efficiency is increased by more than 5 times under the same heat input; the gap compatibility is strong, the assembly gap is allowed to reach 1.5-2.0 mm, the requirements on workpiece groove machining and assembly accuracy are significantly reduced; the heat affected zone is narrow, and the heat affected zone is shortened to 1 / 4 compared with conventional heat affected zone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a welding method and welding wire material for high-pressure hydrogen transmission pipeline steel, as well as applications that can improve the welding efficiency and welding quality of hydrogen transmission pipeline steel, belonging to the field of clean energy. Background Technology

[0002] With the deepening global push towards the goals of "carbon peaking and carbon neutrality," building a new energy system based on renewable energy has become a global consensus. Against this backdrop, hydrogen energy, as an ideal clean secondary energy carrier, has attracted widespread attention. Hydrogen energy refers to the chemical energy released from hydrogen through electrochemical or combustion reactions. Its utilization process only produces water, without generating carbon dioxide or other harmful emissions, making it a truly zero-carbon energy source. Hydrogen has a high mass energy density of 120 MJ / kg, approximately three times the calorific value of standard gasoline. Furthermore, surplus renewable energy can be converted into chemical energy for storage through water electrolysis technology, enabling cross-seasonal and cross-regional energy dispatch and effectively compensating for the limitations of large-scale direct storage in the power system. Simultaneously, hydrogen energy has wide applications in various scenarios. It can be used directly as fuel for transportation, industrial production, and building heating; it can also be used as a chemical raw material in basic chemical industrial processes such as metallurgical reduction, ammonia synthesis, and methanol synthesis; and it can achieve high-efficiency combined heat and power (CHP) through fuel cells, serving as an ideal link between the energy grid and the industrial grid. Therefore, developing the hydrogen energy industry has significant strategic value for optimizing the end-use energy structure, ensuring energy security, and promoting carbon emission reduction in energy-intensive industries.

[0003] In the entire hydrogen energy industry chain, hydrogen production technology is becoming increasingly mature, and the market prospects for hydrogen use are broad. However, storage and transportation have become the core bottleneck restricting the large-scale development of the industry. Hydrogen has an extremely low volumetric energy density; its calorific value per unit volume under standard conditions is only about one-third that of natural gas. Furthermore, hydrogen molecules are extremely small, prone to leakage, and highly flammable and explosive, posing a severe challenge to its safe and efficient transportation. Currently, hydrogen transportation mainly relies on vehicle-mounted methods such as high-pressure gaseous tubular trucks or liquid tank trucks. These methods are suitable for short-distance, small-batch, decentralized hydrogen consumption scenarios, but their inherent shortcomings, such as low transportation efficiency, long loading and unloading times, and high energy loss, severely restrict the economic requirements of a future hydrogen energy supply chain with a capacity of tens of millions of tons. In contrast, pipeline transportation, with its advantages of large capacity, long distance, and low energy consumption, is internationally recognized as the optimal technological route for achieving large-scale, low-cost, and high-efficiency hydrogen transportation. The unit cost of hydrogen transportation via pipeline is only one-tenth to one-fifth that of high-pressure trailer transportation. It also boasts significant advantages such as underground laying, minimal land use, and less susceptibility to climate and environmental factors. Therefore, it is a crucial infrastructure for constructing a national-level hydrogen energy backbone network and achieving effective connectivity between hydrogen energy sources and users. As the physical load-bearing structure of the pipeline, the steel used in hydrogen transportation directly determines the pipeline's transport capacity, service life, and safety level, making it the core material for pipeline hydrogen transportation technology.

[0004] In the construction of high-pressure hydrogen pipelines, welded joints are the weakest links in terms of mechanical properties and microstructure within the entire pipeline system. Pipeline laying inevitably involves numerous circumferential welds. The rapid thermal cycling during welding causes the weld metal and heat-affected zone to undergo complex solid-state phase transformations and microstructural evolution. Problems such as grain coarsening, formation of brittle martensite phases, alloy element burn-off, and micro-segregation are unavoidable, leading to a significant mismatch between strength, plasticity, and toughness in the joint area. Defects introduced by welding, such as residual stress, porosity, slag inclusions, and lack of fusion, as well as numerous dislocations in the coarse-grained region, severely weaken the joint's strength and toughness. Therefore, the efficiency and quality of the welding process directly determine the service safety, service life, and overall integrity of high-pressure hydrogen pipelines, making it one of the core factors restricting the engineering application of hydrogen pipeline technology. Currently, submerged arc welding remains the dominant method in the field of high-pressure hydrogen pipeline welding. However, submerged arc welding has revealed many inherent drawbacks in hydrogen pipeline applications. First, submerged arc welding (SAW) involves excessive heat input, typically reaching 2.5–4.5 kJ / mm for a single weld pass. This results in prolonged high-temperature residence time and slow cooling rates in the weld and heat-affected zone, leading to significant grain coarsening and severely deteriorating joint strength and toughness. Second, the decomposition of flux under the high-temperature arc generates harmful gases such as hydrogen, increasing the diffusible hydrogen content in the weld metal and raising the risk of hydrogen-induced delayed fracture. Third, this process is difficult to apply to automated, high-efficiency welding of pipelines in all positions, and the interpass cleaning and flux recovery during multi-layer, multi-pass welding are cumbersome, limiting construction efficiency.

[0005] To address the aforementioned technical bottlenecks, this invention proposes a laser-MAG hybrid welding process. This process organically couples a high-energy-density laser beam with gas metal arc welding (GMAW), demonstrating significant advantages in welding high-pressure hydrogen pipeline steel. Firstly, laser-MAG hybrid welding offers concentrated energy and controllable heat input (down to 0.5~1.5 kJ / mm), resulting in high welding speed and a narrow heat-affected zone, effectively suppressing excessive grain growth, achieving a fine-grained strengthening effect, and improving the joint's strength and toughness. Secondly, the deep-penetration effect of laser welding significantly enhances penetration depth, increases root penetration, and reduces the number of weld layers; the filling effect of the MAG arc and the droplet transfer characteristics improve weld formation and sidewall fusion, effectively avoiding incomplete fusion and slag inclusions. Furthermore, the synergistic interaction between the laser and the arc stabilizes the molten pool flow behavior, accelerates gas escape, and reduces weld porosity. Therefore, laser-MAG hybrid welding significantly improves the comprehensive mechanical properties of high-pressure hydrogen pipeline joints while ensuring high welding efficiency and excellent forming quality, providing a more reliable technical path for welding hydrogen pipeline engineering. Summary of the Invention

[0006] Purpose of the invention: To provide a high-quality and high-efficiency welding method and welding wire material for hydrogen pipeline steel, providing technical support for the safe transportation of green hydrogen energy.

[0007] Technical Solution: The welding wire material for welding steel in high-pressure hydrogen transmission pipelines according to the present invention comprises, by mass percentage: C: 0.07~0.1%, Si: 0.4~0.8%, Mn: 1~1.7%, P: 0.001~0.01%, S: 0.01~0.03%, Cr: 0.01~0.1%, Mo: 0.2~0.4%, Ni: 0.6~0.9%, Al: 0.01~0.09%, Zr: 0.01~0.05%, balance: Fe; wherein, by mass percentage, the elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula: x1C + x2Mn = x3M o+x4Ni+x5Al+x6Zr, where: x1 represents the solid solution strengthening factor of C element, ranging from 0.98 to 1.02; x2 represents the factor of Mn element inhibiting brittle phase, ranging from -0.0241 to -0.0236; x3 represents the grain refining factor of Mo element, ranging from 0.027 to 0.032; x4 represents the factor of Ni element inhibiting crack propagation, ranging from 0.074 to 0.077; x5 represents the factor of Al element inhibiting laser-induced material damage, ranging from -0.198 to -0.194; and x6 represents the factor of Zr element inhibiting arc-induced material damage, ranging from -0.189 to -0.186.

[0008] The method for preparing the welding wire material of the present invention includes vacuum induction melting, electroslag remelting and refining, hot rolling and Stellmore cooling, and cold drawing processes.

[0009] Vacuum induction melting includes the following steps:

[0010] S1. Place ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium into a vacuum induction melting furnace for smelting. First, preheat and hold the temperature, then gradually increase the temperature until the added metals are completely melted.

[0011] S2. Add lime and refine at high temperature;

[0012] S3. Before casting the steel ingot, nitrogen gas is introduced to cool it down, and vacuum casting is performed to form the steel ingot.

[0013] In step S1, the temperature is first preheated to 300~320℃ and held for 50~60 min, then gradually increased to 1400~1440℃. In step S2, the temperature is refined at 1450~1500℃ for 30~50 min. In step S3, the temperature is lowered to 1400~1420℃ for vacuum casting.

[0014] When performing electroslag remelting, the slag system used is a CaF2-Al2O3-CaO ternary slag system, the remelting current is 750~790A, the voltage is 32~35V, and the melting rate is 2.4~2.9kg / min.

[0015] The welding wire material described in this invention is used in the welding of steel for high-pressure hydrogen transmission pipelines.

[0016] The present invention also includes a welding method for high-pressure hydrogen transmission pipeline steel, characterized in that the welding wire material described in the present invention is used, and the welding is carried out by laser-MAG arc composite welding, and the welding is formed in one pass. The chemical composition of the welding wire, the chemical composition of the pipeline steel, the welding method, and the shielding gas must be compatible with each other.

[0017] Specifically, the following steps are included:

[0018] (1) Grind the welding area of ​​the steel base material of the high-pressure hydrogen transmission pipeline to remove surface stains and oxidation products;

[0019] (2) Welding is performed using a high-power laser and a MAG welding machine;

[0020] (3) The welding wire material described in this invention is fed into the composite welding heat source using a wire feeder, and the CO2 content in the composite welding is adjusted according to the chemical composition of the welding wire material.

[0021] The high-pressure hydrogen pipeline steel contains the following components by mass percentage: C 0.05~0.08%, Si 0.21~0.30%, Mn 1.2~1.9%, P 0.005~0.012%, S 0.002~0.0028%, Nb 0.02~0.04%, Sn 0.01~0.03%, balance Fe, and thickness 10~15 mm. In steps (2) and (3), the welding parameters are: laser power 8000~12000W, welding speed 20~25 mm / s, wire feed speed 9~13 m / min, welding current 240~260 A, welding voltage 25~28 V, defocusing amount -1~-5 mm, and the shielding gas is CO2+Ar with a CO2 volume percentage range of 5~25%. The relative relationship between the volume percentage of CO2 in the shielding gas and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 The formula is Zr + bZr + cAl, where b and c have the following ranges: b represents the binding factor between Zr and reactive oxygen species, ranging from 18.1 to 22.7, and c represents the binding factor between Al and reactive oxygen species, ranging from 89.1 to 95.1. The welded high-pressure hydrogen pipeline steel joint has a yield strength of 570–650 MPa, a tensile strength of 680–750 MPa, an elongation of 25–35%, a Charpy V-shaped impact energy of 251–298 J at 20 °C, and a Charpy V-shaped impact energy of 242–283 J at -20 °C.

[0022] In the welding method of this invention, during the laser-MAG composite heat source welding process, the laser heat source and the electric arc heat source synergistically cooperate in terms of energy density, energy distribution, and CO2 decomposition. Regarding energy density, the laser heat source has extremely high energy density, and the power density of the focused laser beam can reach 10... 6 ~10 7 W / cm 2 The high energy density of lasers allows them to heat the base material to its melting point in a very short time, thus achieving deep penetration welding. In contrast, the energy density of MAG arc heat sources is typically around 10... 4 ~10 5 W / cm 2 From an energy distribution perspective, the energy distribution of a laser heat source is highly concentrated. After focusing, the laser beam forms a very small spot, and the energy exhibits a Gaussian distribution in space, mainly concentrated in the central region of the spot. This results in laser welding having a narrow heat-affected zone and minimal workpiece deformation. In contrast, the energy distribution of a MAG arc heat source is more dispersed. The arc plasma energy exhibits a gradient distribution along the arc's radial direction, with a higher temperature at the center and gradually decreasing towards the periphery. The intervention of the laser significantly alters the energy distribution of the arc—forming a radiation enhancement zone with a large gradient at the center of the arc. The ionization channel of the laser provides a foundation for arc stability, creating a concentrated radiation channel in the central region, concentrating energy in the central area and achieving a greater penetration depth than traditional MAG welding. Simultaneously, the combined effect of the laser and MAG arc can induce CO2 decomposition. In laser-MAG hybrid welding, CO2, as a polyatomic gas, undergoes a decomposition reaction under the high temperature of the laser and arc plasma. CO2 decomposes at high temperatures to form oxygen atoms. The trace amounts of oxygen entering the molten pool alter the surface tension coefficient of the molten metal, thereby changing the flow direction of the molten pool. The electric arc heat source provides a continuous high-temperature plasma environment, which is the main thermodynamic driving force for CO2 decomposition; while the laser heat source itself generates a large amount of plasma, further intensifying the decomposition of CO2. In summary, the laser heat source achieves deep penetration with extremely high energy density and highly concentrated energy distribution, while the MAG arc heat source, with relatively lower energy density and dispersed energy distribution, undertakes the functions of melting the filler metal and controlling the weld width. The combination of the two heat sources not only changes the energy distribution of the arc but also influences the decomposition behavior of the CO2 shielding gas and the flow characteristics of the molten pool through synergistic effects, ultimately achieving welding results superior to those of a single heat source.

[0023] The ultra-rapid cooling rate of the laser-MAG composite heat source induces different strengthening mechanisms for C, Mn, Mo, and Ni elements. Carbon (C): Ultra-rapid cooling inhibits diffusion-type carbon precipitation, causing carbon to exist primarily in supersaturated solid solution form within bainite laths, resulting in a strong solid solution strengthening effect, which is the main source of weld strength. Simultaneously, rapid cooling limits the growth of cementite or alloy carbides, causing the precipitated phases to tend towards nanoscale dispersion, further enhancing precipitation strengthening. Manganese (Mn): Mn is an austenite stabilizing element. Under ultra-rapid cooling conditions, its effect of lowering the martensite initiation temperature (Ms) is more significant, promoting the formation of fine lath martensite or lower bainite in the weld, while refining the original austenite grains, achieving fine-grain strengthening. Mn effectively inhibits the formation of proeutectoid ferrite and promotes the nucleation of tough acicular ferrite, improving toughness while ensuring strength. Molybdenum (Mo): Mo has strong hardenability and a tendency to form carbides. Ultrafast cooling strongly inhibits Mo diffusion, promoting the formation of finer bainitic laths or martensite-austenite (MA) components. Mo refines lath bundle width and maintains good ductility and toughness at ultra-high strength through the synergistic effect of solid solution strengthening and precipitation strengthening. Nickel (Ni): Primarily increases strength through solid solution strengthening. Ni strongly stabilizes austenite, retaining a thin film of residual austenite between laths. This film-like residual austenite effectively blunts crack tips, significantly improving the low-temperature toughness and fracture resistance of the weld. Ni lowers stacking fault energy, hindering dislocation cross-slip and increasing work hardening rate. Ultrafast cooling also inhibits Ni segregation, homogenizing the microstructure, thus significantly improving impact toughness while enhancing strength, making it a key element for achieving a high-strength, high-toughness balance. Aluminum (Al): Al is a strong deoxidizing element, preferentially reacting with dissolved oxygen in the laser-MAG composite welding pool to form high-melting-point Al2O3 inclusions. Under ultrafast cooling conditions, Al₂O₃ particles nucleate and are rapidly frozen, making them difficult to aggregate and grow, and thus dispersed in the weld matrix at a submicron scale. These fine oxides act as heterogeneous nucleation sites for acicular ferrite, inducing intragranular refinement and significantly improving toughness. Simultaneously, the deoxidation reaction reduces the free oxygen content in the molten pool, inhibiting the formation of CO pores and brittle oxides, and purifying the weld metal. Zirconium (Zr): Zr has a stronger deoxidizing ability than Al, preferentially reacting with oxygen decomposed in the laser-MAG composite weld to form extremely stable, high-melting-point (approximately 2700℃) ZrO₂ particles. Under the high energy density and strong convection stirring of the composite welding, ZrO₂ particles are uniformly dispersed throughout the molten pool. These fine ZrO₂ particles not only pin grain boundaries and prevent austenite grain growth, but also, due to their good lattice matching with ferrite, become the most effective nucleating agent for acicular ferrite, significantly refining the weld microstructure and improving low-temperature impact toughness. Furthermore, Zr reduces the surface tension of the molten pool, improves wettability, and promotes molten pool spreading. In a trace oxygen environment, the synergistic effect of Zr's deoxidation and nucleation is key to improving the overall performance of the weld.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention has high welding efficiency. By combining laser and MAG arc off-axis, it achieves the synergistic effect of high energy density and wide weld width. Under the same heat input, the welding efficiency is more than 5 times higher than that of submerged arc welding. It has strong gap compatibility. Arc-assisted heating can effectively make up for the high gap sensitivity of laser. It allows the assembly gap to reach 1.5~2.0 mm, which significantly reduces the requirements for workpiece beveling and assembly accuracy. The heat-affected zone is narrow. Compared with conventional submerged arc welding, the heat-affected zone is shortened to 1 / 4. (2) The present invention makes full use of the laser-arc composite heat source, the welding metallurgical behavior of C / Mn / Mo / Ni / Al / Zr elements, and the decomposition and oxidation of CO2 in the composite heat source. It organically combines the three to form a 1+1+1>3 effect. Attached Figure Description

[0025] Figure 1 The macroscopic cross-sectional morphology of the laser-MAG composite welding specimen prepared in Example 1;

[0026] Figure 2 The images show the microstructure of the laser and arc regions of the laser-MAG weld seam prepared in Example 1; where a represents the laser region and b represents the arc region. Detailed Implementation

[0027] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0028] Example 1

[0029] (1) Preparation of welding wire material:

[0030] The welding wire composition in this embodiment, by mass percentage, is as follows: C: 0.07%, Si: 0.5%, Mn: 1.1%, P: 0.002%, S: 0.01%, Cr: 0.03%, Mo: 0.21%, Ni: 0.6%, Al: 0.02%, Zr: 0.01%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr, by mass percentage, satisfy the following formula: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 1.01, -0.0239, 0.027, 0.074, -0.194, and -0.186, respectively.

[0031] Based on the welding wire composition, the process involves vacuum induction melting, electroslag remelting refining, hot rolling, Stellmore cooling, and cold drawing. High-purity raw materials such as ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, high-purity metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium are placed in a vacuum induction melting furnace for smelting. The required weight of raw materials is calculated using the following formula: Amount of a certain element added = (Total mass of molten steel * Content of the certain element / Yield of the element) / Content of the element in the alloy. The yields of Ni, Mo, Cr, Mn, Si, Al, Zr, and Fe are 98%, 97%, 91%, 88%, 92%, 91%, 90%, and 99%, respectively. Through the above steps, the designed welding wire composition can be accurately obtained.

[0032] S1. Place the above high-purity raw materials into a vacuum induction furnace, preheat to 300 ℃ and keep warm for 50 min, and gradually increase the temperature to 1410 ℃ until the raw materials are completely melted.

[0033] S2. Add lime to adjust the sulfur and phosphorus content to the design value, refine at 1460℃ and hold for 32 minutes, introduce high-purity nitrogen before casting, and vacuum cast into steel ingots when the temperature drops to 1400℃.

[0034] S3. Electroslag remelting was performed using a CaF2-Al2O3-CaO ternary slag system with a remelting current of 760 A, a voltage of 32 V, and a melting rate of 2.4 kg / min.

[0035] S4. The steel ingot is then fed into a hot continuous rolling mill for rolling, and after being cooled in Stellmore, it becomes a hot-rolled wire coil. After removing the surface iron oxide scale, it undergoes multiple cold drawing passes, and is finally cold-drawn into a welding wire with a diameter of 1.2 mm.

[0036] (2) Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0037] The composition of the high-pressure hydrogen transmission pipeline steel by mass percentage is as follows: C: 0.06%, Si: 0.23%, Mn: 1.5%, P: 0.007%, S: 0.0022%, Nb: 0.02%, Sn: 0.01%, balance Fe.

[0038] The welding surface of the 10 mm thick high-pressure hydrogen pipeline steel was polished using metallographic sandpaper to remove surface stains and oxidation products. A high-power laser and a MAG welding machine were then used to weld the pipeline steel base material. The laser and MAG welding machine operated in tandem, performing single-sided welding with double-sided forming in a single pass. The high-power laser was adjusted to 8000 W, the welding speed was controlled by a robot at 21 mm / s, the wire feeder was set to a wire feed speed of 9.9 m / min, the MAG welding machine was set to a welding current of 246 A, a welding voltage of 26 V, a defocusing depth of -2 mm, and a shielding gas of CO2 + Ar with a CO2 volume percentage of 7.17%. The relative relationship between the CO2 volume percentage of the shielding gas and the mass percentages of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where the values ​​of b and c are 22.5 and 94.2, respectively.

[0039] The macroscopic cross-sectional morphology of the joint manufactured using the above welding wire and welding method is as follows: Figure 1 As shown, the microstructure is as follows Figure 2 As shown, mechanical property tests were performed on the modified welded specimen, and the yield strength, tensile strength, and elongation of the joint were obtained as 580 MPa, 700 MPa, and 26%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimen at 20℃ and -20℃ was measured to be 259 J and 247 J, respectively.

[0040] Example 2

[0041] The welding wire preparation process is the same as in Example 1, except that the welding wire components involved in this example are as follows by mass percentage: C: 0.08%, Si: 0.6%, Mn: 1.3%, P: 0.003%, S: 0.02%, Cr: 0.06%, Mo: 0.28%, Ni: 0.7%, Al: 0.03%, Zr: 0.04%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula by mass percentage: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 0.99, -0.0237, 0.03, 0.076, -0.195, and -0.187, respectively.

[0042] Based on the welding wire composition, the process involves vacuum induction melting, electroslag remelting refining, hot rolling, Stellmore cooling, and cold drawing. High-purity raw materials such as ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, high-purity metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium are placed in a vacuum induction melting furnace for smelting to precisely obtain the designed welding wire composition.

[0043] S1. Place the above high-purity raw materials into a vacuum induction furnace, preheat to 350 ℃ and hold for 52 min, and gradually increase the temperature to 1400 ℃ until the raw materials are completely melted.

[0044] S2. Add lime to adjust the sulfur and phosphorus content to the design value, refine at 1457℃ and hold for 42 minutes, introduce high-purity nitrogen before casting, and vacuum cast into steel ingots when the temperature drops to 1410℃.

[0045] S3. Electroslag remelting was performed using a CaF2-Al2O3-CaO ternary slag system with a remelting current of 765 A, a voltage of 33 V, and a melting rate of 2.6 kg / min.

[0046] S4. The steel ingot is then fed into a hot continuous rolling mill for rolling, and after being cooled in Stellmore, it becomes a hot-rolled wire coil. After removing the surface iron oxide scale, it undergoes multiple cold drawing passes, and is finally cold-drawn into a welding wire with a diameter of 1.2 mm.

[0047] (2) Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0048] The experimental procedure was the same as in Example 1, except that the composition of the 10 mm thick high-pressure hydrogen pipeline steel by mass percentage was as follows: C: 0.07%, Si: 0.26%, Mn: 1.8%, P: 0.008%, S: 0.0026%, Nb: 0.03%, Sn: 0.01%, balance Fe.

[0049] During welding, the laser power was adjusted to 8900 W, the welding speed was controlled by a robot at 22 mm / s, the wire feeder speed was set to 10.9 m / min, the MAG welding machine was set to a welding current of 249 A, a welding voltage of 26 V, a defocusing depth of -2.5 mm, and a shielding gas of CO2 + Ar with a CO2 volume percentage of 16.38%. The relative relationship between the CO2 volume percentage of the shielding gas and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where b and c have values ​​of 18 and 90, respectively.

[0050] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 583 MPa, 710 MPa, and 27%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 255 J and 247 J, respectively.

[0051] Example 3

[0052] The welding wire preparation process is the same as in Example 1, except that the welding wire components involved in this example are as follows by mass percentage: C: 0.09%, Si: 0.7%, Mn: 1.7%, P: 0.003%, S: 0.02%, Cr: 0.06%, Mo: 0.35%, Ni: 0.77%, Al: 0.05%, Zr: 0.05%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula by mass percentage: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 1.0, -0.0239, 0.031, 0.075, -0.196, and -0.188, respectively.

[0053] Based on the welding wire composition, the process involves vacuum induction melting, electroslag remelting refining, hot rolling, Stellmore cooling, and cold drawing. High-purity raw materials such as ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, high-purity metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium are placed in a vacuum induction melting furnace for smelting to precisely obtain the designed welding wire composition.

[0054] S1. Place the above high-purity raw materials into a vacuum induction furnace, preheat to 312 ℃ and hold for 55 min, and gradually increase the temperature to 1430 ℃ until the raw materials are completely melted.

[0055] S2. Add lime to adjust the sulfur and phosphorus content to the design value, refine at 1457℃ and hold for 45 minutes, introduce high-purity nitrogen before casting, and vacuum cast into steel ingots when the temperature drops to 1413℃.

[0056] S3. Electroslag remelting was performed using a CaF2-Al2O3-CaO ternary slag system with a remelting current of 772 A, a voltage of 35 V, and a melting rate of 2.9 kg / min.

[0057] S4. The steel ingot is then fed into a hot continuous rolling mill for rolling, and after being cooled in Stellmore, it becomes a hot-rolled wire coil. After removing the surface iron oxide scale, it undergoes multiple cold drawing passes, and is finally cold-drawn into a welding wire with a diameter of 1.2 mm.

[0058] (2) Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0059] The experimental procedure was the same as in Example 1, except that the composition of the 10 mm thick high-pressure hydrogen pipeline steel by mass percentage was as follows: C: 0.07%, Si: 0.24%, Mn: 1.4%, P: 0.006%, S: 0.0022%, Nb: 0.03%, Sn: 0.03%, balance Fe.

[0060] During welding, the laser power was adjusted to 9100 W, the welding speed was controlled by a robot at 23 mm / s, the wire feeder speed was set to 11 m / min, the MAG welding machine welding current was set to 248 A, the welding voltage to 25 V, the defocusing amount to -3 mm, and the shielding gas to be CO2 + Ar with a CO2 volume percentage of 22.56%. The relative relationship between the CO2 volume percentage and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where the values ​​of b and c are 18.5 and 90.5, respectively.

[0061] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 583 MPa, 720 MPa, and 29%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 273 J and 267 J, respectively.

[0062] Example 4

[0063] The welding wire preparation process is the same as in Example 1, except that the welding wire components involved in this example are as follows by mass percentage: C: 0.095%, Si: 0.7%, Mn: 1.6%, P: 0.006%, S: 0.02%, Cr: 0.08%, Mo: 0.4%, Ni: 0.82%, Al: 0.06%, Zr: 0.03%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula by mass percentage: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 1.01, -0.024, 0.032, 0.076, -0.198, and -0.189, respectively.

[0064] Based on the welding wire composition, the process involves vacuum induction melting, electroslag remelting refining, hot rolling, Stellmore cooling, and cold drawing. High-purity raw materials such as ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, high-purity metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium are placed in a vacuum induction melting furnace for smelting to precisely obtain the designed welding wire composition.

[0065] S1. Place the above high-purity raw materials into a vacuum induction furnace, preheat to 316 ℃ and hold for 60 min, and gradually increase the temperature to 1440 ℃ until the raw materials are completely melted.

[0066] S2. Add lime to adjust the sulfur and phosphorus content to the design value, refine at 1479 ℃ and hold for 42 min, introduce high-purity nitrogen gas before casting, and vacuum cast into steel ingots when the temperature drops to 1412 ℃.

[0067] S3. Electroslag remelting was performed using a CaF2-Al2O3-CaO ternary slag system with a remelting current of 781 A, a voltage of 34 V, and a melting rate of 2.8 kg / min.

[0068] S4. The steel ingot is then fed into a hot continuous rolling mill for rolling, and after being cooled in Stellmore, it becomes a hot-rolled wire coil. After removing the surface iron oxide scale, it undergoes multiple cold drawing passes, and is finally cold-drawn into a welding wire with a diameter of 1.2 mm.

[0069] (2) Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0070] The experimental procedure was the same as in Example 1, except that the composition of the 10 mm thick high-pressure hydrogen pipeline steel by mass percentage was as follows: C: 0.08%, Si: 0.28%, Mn: 1.8%, P: 0.006%, S: 0.0021%, Nb: 0.04%, Sn: 0.02%, balance Fe.

[0071] During welding, the laser power was adjusted to 11000 W, the welding speed was controlled by a robot at 23 mm / s, the wire feeder speed was set to 12.1 m / min, the MAG welding machine was set to a welding current of 252 A, a welding voltage of 27 V, a defocusing depth of -3.5 mm, and a shielding gas of CO2 + Ar with a CO2 volume percentage of 19.38%. The relative relationship between the CO2 volume percentage of the shielding gas and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where b and c have values ​​of 21 and 92 respectively.

[0072] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 590 MPa, 710 MPa, and 29%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 286 J and 271 J, respectively.

[0073] Example 5

[0074] The welding wire preparation process is the same as in Example 1, except that the welding wire components involved in this example are as follows by mass percentage: C: 0.09%, Si: 0.8%, Mn: 1.65%, P: 0.006%, S: 0.02%, Cr: 0.09%, Mo: 0.38%, Ni: 0.75%, Al: 0.06%, Zr: 0.043%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula by mass percentage: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 0.98, -0.0236, 0.029, 0.077, -0.196, and -0.186, respectively.

[0075] Based on the welding wire composition, the process involves vacuum induction melting, electroslag remelting refining, hot rolling, Stellmore cooling, and cold drawing. High-purity raw materials such as ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, high-purity metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium are placed in a vacuum induction melting furnace for smelting to precisely obtain the designed welding wire composition.

[0076] S1. Place the above high-purity raw materials into a vacuum induction furnace, preheat to 318 ℃ and hold for 54 min, and gradually increase the temperature to 1420 ℃ until the raw materials are completely melted.

[0077] S2. Add lime to adjust the sulfur and phosphorus content to the design value, refine at 1483 ℃ and hold for 42 min, introduce high-purity nitrogen before casting, and vacuum cast into steel ingot when the temperature drops to 1418 ℃.

[0078] S3. Electroslag remelting was performed using a CaF2-Al2O3-CaO ternary slag system with a remelting current of 782 A, a voltage of 33 V, and a melting rate of 2.6 kg / min.

[0079] S4. The steel ingot is then fed into a hot continuous rolling mill for rolling, and after being cooled in Stellmore, it becomes a hot-rolled wire coil. After removing the surface iron oxide scale, it undergoes multiple cold drawing passes, and is finally cold-drawn into a welding wire with a diameter of 1.2 mm.

[0080] (2) Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0081] The experimental procedure was the same as in Example 1, except that the composition of the 10 mm thick high-pressure hydrogen pipeline steel by mass percentage was as follows: C: 0.07%, Si: 0.29%, Mn: 1.9%, P: 0.006%, S: 0.0021%, Nb: 0.03%, Sn: 0.02%, balance Fe.

[0082] During welding, the laser power was adjusted to 11500 W, the welding speed was controlled by a robot at 24 mm / s, the wire feeder speed was set to 12.3 m / min, the MAG welding machine welding current was set to 254 A, the welding voltage to 27 V, the defocusing amount to -3 mm, and the shielding gas to be CO2 + Ar with a CO2 volume percentage of 20.37%. The relative relationship between the CO2 volume percentage of the shielding gas and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where the values ​​of b and c are 18.2 and 89, respectively.

[0083] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 623 MPa, 741 MPa, and 31%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 288 J and 261 J, respectively.

[0084] Comparative Example 1

[0085] The composition and preparation process of the welding wire are the same as in Example 1. The welding wire components, by mass percentage, are: C: 0.07%, Si: 0.5%, Mn: 1.1%, P: 0.002%, S: 0.01%, Cr: 0.03%, Mo: 0.21%, Ni: 0.6%, Al: 0.02%, Zr: 0.01%, with the balance being Fe. The elements C, Mn, Mo, Ni, Al, and Zr, by mass percentage, satisfy the following formula: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where the values ​​of x1 to x6 are 1.01, -0.0239, 0.027, 0.074, -0.194, and -0.186, respectively.

[0086] Welding of high-pressure hydrogen transport pipeline steel using the welding wire material prepared in step (1):

[0087] The experimental procedure was the same as in Example 1, except that the 10 mm thick high-pressure hydrogen pipeline steel used was the conventional pipeline steel with the chemical composition disclosed in CN122382476A, and the composition by mass percentage was as follows: C: 0.042%, Si: 0.26%, Mn: 1.54%, P: 0.007%, S: 0.0011%, Nb: 0.055%, Cr: 0.46%, Ni: 0.48%, Mo: 0.22%, V: 0.039%, Ti: 0.015%, N: 0.004%, balance Fe.

[0088] During welding, the laser power was adjusted to 8000 W, the welding speed was controlled by a robot at 21 mm / s, the wire feeder speed was set to 9.9 m / min, the MAG welding machine was set to a welding current of 246 A, a welding voltage of 26 V, a defocusing depth of -2 mm, and a shielding gas of CO2 + Ar with a CO2 volume percentage of 7.17%. The relative relationship between the CO2 volume percentage of the shielding gas and the mass percentage of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where the values ​​of b and c are 22.5 and 94.2, respectively.

[0089] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 510 MPa, 540 MPa, and 19%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 183 J and 162 J, respectively.

[0090] Compared to Example 1, this comparative example simply replaces the chemical composition of the hydrogen pipeline steel with that of conventional pipeline steel (see CN122382476A), uses the same welding wire and welding process to manufacture the base material, and the yield strength, tensile strength, and elongation of the joint are significantly reduced. The Charpy V-notch impact energy values ​​of the joint at 20°C and -20°C are also significantly reduced. This demonstrates that the chemical composition of the welding wire, the welding process, and the CO2 content in this invention are correlated.

[0091] Comparative Example 2

[0092] (1) The composition and preparation process of the welding wire are the same as in Example 1. The components of the welding wire are as follows by mass percentage: C: 0.07%, Si: 0.5%, Mn: 1.1%, P: 0.002%, S: 0.01%, Cr: 0.03%, Mo: 0.21%, Ni: 0.6%, Al: 0.02%, Zr: 0.01%, balance Fe. The elements of C, Mn, Mo, Ni, Al and Zr satisfy the following formula by mass percentage: x1C+x2Mn=x3Mo+x4Ni+x5Al+x6Zr, where the values ​​of x1~x6 are 1.01, -0.0239, 0.027, 0.074, -0.194 and -0.186, respectively.

[0093] Welding was performed using the welding wire material prepared in step (1) according to the conventional submerged arc welding method disclosed in CN115922035A:

[0094] The experimental procedure was the same as in Example 1. The 10 mm thick high-pressure hydrogen pipeline steel-timber material was the same as in Example 1, with the following composition by mass percentage: C: 0.06%, Si: 0.23%, Mn: 1.5%, P: 0.007%, S: 0.0022%, Nb: 0.02%, Sn: 0.01%, balance Fe. The difference was that conventional submerged arc welding was used, employing an X-groove. The inner side welding was completed in two passes: the first pass had a welding current of 600A and a voltage of 34V, and the second pass had a welding current of 450A and a voltage of 36V. The outer side was also completed in two passes: the first pass had a welding current of 810A and a welding voltage of 36V, and the second pass had a welding current of 620A and a welding voltage of 38V. Because submerged arc welding uses a protective flux to isolate the air, no shielding gas was required.

[0095] The joints manufactured using the aforementioned welding wire and submerged arc welding method were subjected to mechanical property tests, and the yield strength, tensile strength, and elongation of the joints were found to be 512 MPa, 593 MPa, and 12%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 162 J and 152 J, respectively.

[0096] Compared to Example 1, simply replacing the laser-MAG composite welding in this application with submerged arc welding (CNCN115922035A), a method commonly used for pipeline steel, and using the same welding wire and base material as in Example 1, results in a decrease in the yield strength, tensile strength, and elongation of the joint. Furthermore, the Charpy V-notch impact energy values ​​at 0°C and -20°C do not meet the design requirements. This demonstrates that the chemical composition of the welding wire in this invention must be matched with the welding process; simply migrating the welding method will not yield satisfactory results.

[0097] Comparative Example 3

[0098] The welding process is the same as in Example 1, except that the welding wire used is the submerged arc welding wire for hydrogen pipeline steel disclosed in CN120438892A. The composition of the welding wire by mass percentage is: C: 0.09%, Si: 0.39%, Mn: 1.41%, P: 0.005%, S: 0.003%, Mo: 0.15%, Ni: 0.73%, V: 0.016%, Ti: 0.06%, Nb: 0.08%, Ce: 0.018%, balance Fe.

[0099] The joint manufactured using the above-mentioned welding wire and the welding method of the present invention was subjected to mechanical property testing. The yield strength, tensile strength, and elongation of the joint were found to be 488 MPa, 532 MPa, and 13%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured sample at 20°C and -20°C was measured to be 135 J and 115 J, respectively.

[0100] Compared to Example 1, when the base material of this application is welded using the disclosed submerged arc welding wire for hydrogen pipeline steel (CN120438892A) and the laser-MAG composite welding method described in this application is used, the yield strength, tensile strength, and elongation of the joint will significantly decrease, and the impact energy will also be greatly reduced. Therefore, it is evident that the laser-MAG composite welding process in this invention requires compatibility with the welding wire composition; simply replacing the welding wire will not achieve the desired results.

[0101] Comparative Example 4

[0102] The welding process is the same as in Example 1, except that the welding wire composition by mass percentage is: C: 0.1%, Si: 0.6%, Mn: 1.6%, P: 0.002%, S: 0.01%, Cr: 0.08%, Mo: 0.31%, Ni: 0.8%, Al: 0.02%, Zr: 0.01%, with the balance being Fe. The C, Mn, Mo, Ni, Al, and Zr elements by mass percentage do not satisfy the formula x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, and the values ​​of x1 to x6 satisfy the following ranges: x1 0.98~1.02, x2 -0.0236~-0.0241, x3 0.027~0.032, x4 0.074-0.077, x5 -0.194~-0.198, x6 -0.186~-0.189.

[0103] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 470 MPa, 530 MPa, and 12%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 172 J and 138 J, respectively.

[0104] Compared to Example 1, the chemical composition of the welding wire was changed based on publicly available knowledge. The contents of C, Mn, Mo, Ni, Al, and Zr did not meet the requirements of the design formula of this invention, resulting in a significant decrease in the joint's yield strength, tensile strength, elongation, and impact energy. Therefore, it is evident that the chemical composition of the welding wire in this invention is designed based on the characteristics of the laser-MAG composite welding heat source, the base alloy composition, and welding parameters. Simply changing the chemical composition of the welding wire mechanically does not yield satisfactory results.

[0105] Comparative Example 5

[0106] The welding process is the same as in Example 1, except that the welding wire components are composed of conventional materials, with the following mass percentages: C: 0.12%, Si: 0.3%, Mn: 1.9%, P: 0.012%, S: 0.06%, Cr: 0.03%, Mo: 0.82%, Ni: 1.24%, Al: 0.12%, Zr: 0.08%, with the balance being Fe. The mass percentages of C, Mn, Mo, Ni, Al, and Zr satisfy the formula x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, where x1 to x6 are 1.01, -0.0239, 0.027, 0.074, -0.194, and -0.186, respectively.

[0107] The joint manufactured using the above-mentioned welding wire and the welding method of the present invention was subjected to mechanical property testing. The yield strength, tensile strength, and elongation of the joint were found to be 430 MPa, 503 MPa, and 10%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured sample at 20°C and -20°C was measured to be 162 J and 125 J, respectively.

[0108] Compared to Example 1, simply adjusting the chemical composition of the welding wire using publicly available conventional knowledge, even if it meets the design formula x1C + x2Mn = x3Mo + x4Ni + x5Al + x6Zr, results in a significant change in the welding wire's chemical composition. This leads to a substantial decrease in the joint's yield strength, tensile strength, elongation, and impact energy. Therefore, the welding wire composition in this invention must be matched to the laser-MAG welding process, and the specific composition content of the welding wire needs to be under certain limited conditions to achieve better technical results.

[0109] Comparative Example 6

[0110] The welding wire and welding process are the same as in Example 1, except that the CO2 volume percentage is 21% during welding, and the relative relationship between the CO2 volume percentage of the shielding gas and the mass percentage of Al and Zr in the welding wire material does not satisfy the formula CO2=b 2 Zr+bZr+cAl.

[0111] The joints manufactured using the aforementioned welding wire and welding method were subjected to mechanical property tests, yield strength, tensile strength, and elongation of 453 MPa, 518 MPa, and 14%, respectively. A V-notch was prepared at the weld location, and Charpy impact tests were conducted. The impact energy of the manufactured specimens at 20℃ and -20℃ were measured to be 165 J and 143 J, respectively.

[0112] Compared to Example 1, simply changing the CO2 volume percentage without considering the Al and Zr mass percentages in the welding wire also resulted in a decrease in mechanical properties. Therefore, the CO2 content in this invention needs to be comprehensively evaluated in conjunction with the characteristics of the laser-MAG welding composite heat source and the Al and Zr content in the welding wire; mechanically changing the CO2 volume percentage cannot achieve the desired results.

Claims

1. A welding wire material for welding steel in high-pressure hydrogen transmission pipelines, characterized in that, The composition, by mass percentage, includes C: 0.07~0.1%, Si: 0.4~0.8%, Mn: 1~1.7%, P: 0.001~0.01%, S: 0.01~0.03%, Cr: 0.01~0.1%, Mo: 0.2~0.4%, Ni: 0.6~0.9%, Al: 0.01~0.09%, Zr: 0.01~0.05%, with the balance being Fe; wherein, by mass percentage, the elements C, Mn, Mo, Ni, Al, and Zr satisfy the following formula: x1C + x2Mn = x3Mo + x4Ni + x5Al + x6 Zr, where: x1 represents the solid solution strengthening factor of C element, ranging from 0.98 to 1.02; x2 represents the factor of Mn element inhibiting brittle phase, ranging from -0.0241 to -0.0236; x3 represents the grain refining factor of Mo element, ranging from 0.027 to 0.032; x4 represents the factor of Ni element inhibiting crack propagation, ranging from 0.074 to 0.077; x5 represents the factor of Al element inhibiting laser-induced material damage, ranging from -0.198 to -0.194; and x6 represents the factor of Zr element inhibiting arc-induced material damage, ranging from -0.189 to -0.

186.

2. The method for preparing the welding wire material according to claim 1, characterized in that, The process includes vacuum induction melting, electroslag remelting and refining, hot rolling and Stellmor cooling, and cold drawing. Vacuum induction melting includes the following steps: S1. Place ultra-low carbon pure iron, electrolytic nickel, ferromanganese, ferrosilicon, metallic chromium, ferromolybdenum, metallic aluminum, and metallic zirconium into a vacuum induction melting furnace for smelting. First, preheat and hold the temperature, then gradually increase the temperature until the added metals are completely melted. S2. Add lime and refine at high temperature; S3. Before casting the steel ingot, nitrogen gas is introduced to cool it down, and vacuum casting is performed to form the steel ingot.

3. The preparation method according to claim 2, characterized in that, In step S1, the temperature is first preheated to 300~320℃ and held for 50~60 min, then gradually increased to 1400~1440℃. In step S2, the temperature is refined at 1450~1500℃ for 30~50 min. In step S3, the temperature is lowered to 1400~1420℃ for vacuum casting.

4. The preparation method according to claim 2, characterized in that, When performing electroslag remelting, the slag system used is a CaF2-Al2O3-CaO ternary slag system, the remelting current is 750~790A, the voltage is 32~35V, and the melting rate is 2.4~2.9kg / min.

5. The application of the welding wire material of claim 1 in the welding of high-pressure hydrogen transmission pipeline steel.

6. A welding method for high-pressure hydrogen transmission pipeline steel, characterized in that, Using the welding wire material described in claim 1, the welding is performed via a laser-MAG arc hybrid welding method, and the welding is completed in one pass.

7. The welding method according to claim 6, characterized in that, The high-pressure hydrogen pipeline steel contains the following components by mass percentage: C 0.05~0.08%, Si 0.21~0.30%, Mn 1.2~1.9%, P 0.005~0.012%, S 0.002~0.0028%, Nb 0.02~0.04%, Sn 0.01~0.03%, balance Fe.

8. The welding method according to claim 6, characterized in that, The welding parameters are as follows: laser power 8000~12000W, welding speed 20~25 mm / s, wire feed speed 9~13 m / min, welding current 240~260 A, welding voltage 25~28V, defocusing amount -1~-5 mm, shielding gas is CO2+Ar, and CO2 volume percentage range is 5~25%.

9. The welding method according to claim 8, characterized in that, The relative relationship between the volume percentage of CO2 in the shielding gas and the mass percentages of Al and Zr in the welding wire material satisfies the following formula: CO2 = b 2 Zr+bZr+cAl, where b represents the binding factor of Zr with reactive oxygen species, ranging from 18.1 to 22.7, and c represents the binding factor of Al with reactive oxygen species, ranging from 89.1 to 95.

1.

10. The welding method according to claim 6, characterized in that, The welded high-pressure hydrogen pipeline steel joint has a yield strength of 570~650 MPa, a tensile strength of 680-750 MPa, an elongation of 25~35%, a Charpy V-shaped impact energy of 251~298 J at 20 ℃, and a Charpy V-shaped impact energy of 242~283 J at -20 ℃.

Citation Information

Patent Citations

  • Welding method for thin-gauge pipeline steel plate

    CN115922035A

  • Submerged arc welding wire for X65 hydrogen transmission pipeline steel

    CN120438892A

  • Thick-gauge pipeline steel with excellent low-temperature toughness and production method thereof

    CN122382476A